EFFICIENCY ANALYSIS ON TRADITIONAL MARKET IN SALATIGA, AN APPLICATION OF DATA ENVELOPMENT ANALYSIS - Lintangsari Susanto Putri; Evi Gravitiani (MESP–FEB UNS, 2020)
Salatiga City is one of the cities in Jawa Tengah that has revitalized all traditional markets. The research objective was to analyze the comparison of the efficiency level of traditional markets in Salatiga. The quantitative research method with the analytical tool used is the Data Envelopment Analysis model of Charnes, Cooper, and Rhodes (CCR). The research object is eight traditional markets in Salatiga City. The dependent variable of this research is the efficiency value of traditional markets in the City of Salatiga. The independent variables in this study include two variables, namely the input and output variables. Research findings when data collection is that the two UPTDs as market managers have different categories of managed market management. The results of the study were that the eight markets had different results. The results of four markets are efficiency, two markets have inefficiency results, and two markets cannot be analyzed. Research suggestion is to achieve efficiency in traditional markets that are not efficient can be achieved when referring to market value efficiency.Keywords: Data Envelopment Analysis (DEA), CCR models, Traditional market